Quadruple Helix-Based Early Warning System for Socio-Religious Conflict in East Lombok - Wiredarme; Muhammad Suhardi; Abdul Wahab (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to analyze the early warning system for socio-religious conflict in East Lombok Regency, identify barriers to Quadruple Helix collaboration, and formulate a contextual and implementable model for strengthening early conflict detection. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving local government officials, district and village authorities, academics, local media, and religious organization leaders. The data were analyzed using thematic analysis to identify key patterns related to the existing early warning system, collaboration barriers, and the required strengthening model. The findings show that the early warning system for socio-religious conflict in East Lombok has operated through territorial networks, social communication, community reports, the role of religious leaders, and the intelligence network of the National Unity and Politics Agency at the village level. However, the system has not yet been fully institutionalized, as it lacks standardized reporting mechanisms, an integrated database, risk classification, and regular cross-actor analytical forums. The main barriers include structural barriers in the form of institutional fragmentation, cultural barriers related to strong sensitivity toward religious symbols and intergroup prejudice, and coordinative barriers caused by the absence of a permanent collaborative forum. This study recommends a Socio-Religious Early Warning Model based on Quadruple Helix and Social Resilience, integrating the roles of government, academia, media, and civil society through early monitoring, information validation, risk classification, preventive intervention, public communication, evaluation, and social recovery. This model emphasizes that conflict prevention cannot rely solely on a security-based approach, but must connect administrative legality, social legitimacy, academic analysis, public communication, and community participation.